France : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, Payment Systems, Securities Settlement, and Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2004)
This Financial System Stability Assessment on France reviews the institutional and regulatory framework. Consolidation among financial institutions has resulted in six large universal, vertically integrated banking groups having a strong position in the domestic market. Bank profitability has improved markedly over the past decade and is in line with average euro area levels. Systemic vulnerabilities in the important insurance sector are well contained. The government debt market is large, and the corporate debt market has been growing rapidly since the introduction of the euro.